The Impact of Financial Literacy on SMEs Performance: The Role of Access to Financial Resources as a Mediator - Wati, Kristin Lita; Sianturi, Murdan; Liswatin, Liswatin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines the relationship between financial literacy and the performance of Small and Medium Enterprises (SMEs), with a specific focus on the mediating role of access to financial resources. The research aims to explore how financial literacy influences SME performance both directly and indirectly through improved access to financing. Data was collected from 150 SME owners and managers in Kendari, Indonesia, using structured questionnaires. The results show that financial literacy positively impacts both access to financial resources and SME performance. Additionally, access to financial resources was found to mediate the relationship between financial literacy and SME performance. These findings highlight the importance of financial literacy in enhancing business outcomes and facilitating access to capital for SMEs. The study suggests that improving financial literacy among SME owners is crucial for fostering sustainable business growth, and that both financial education and easier access to finance should be prioritized by policymakers and financial institutions